Пустые земли: фантастический роман / Алексей Калугин - Калугин Алексей Александрович (S.T.A.L.K.E.R., 2009)
Экземпляры: аб. (20180412) / Инвентарный номер: 58242 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445